Penguatan Literasi Budaya Bagi Guru di Sekolah Indonesia Bangkok Untuk Meningkatkan Pemahaman Multikultural Dalam Pembelajaran - Ali Mustadi; Setiawan Edi Wibowo; Sandy Abdi Kusumah; Evy Nur Rochmah (Pusat Riset dan Inovasi Nasional, 2025)
The Indonesian School in Bangkok is a school based in Bangkok, adopting the Indonesian education system. Schools abroad established by Indonesia must adhere to the same educational system as Indonesia, from curriculum design to implementation. The Indonesian education system is inseparable from cultural inculcation. This also underpins curriculum development, emphasizing the importance of Indonesian culture in learning, ensuring that culture is preserved and not lost. Indonesia's rich cultural diversity impacts the norms inherent in students and their families, making it crucial. Therefore, Cultural Literacy Strengthening Training for Teachers at the Indonesian School in Bangkok is essential to enhance multicultural understanding in learning. This strengthening training aims to enhance teachers' understanding of the concept of cultural literacy and how to integrate it into learning. It also helps teachers integrate Indonesian, Thai, and global cultural values ​​into teaching materials.